Visualization of vesicular transport from the endoplasmic reticulum to lysosome using an amidine derived two-photon probe. Issue 45 (22nd May 2017) - Lee, Hyo Won; Cho, Myoung Ki; Kim, Hye-Ri; Lim, Chang Su; Kang, Chulhun; Kim, Hwan Myung
Abstract : An amidine-based small molecule two-photon fluorescent probe for monitoring vesicle transport from the ER to lysosome in live cells was reported. Abstract : We report an amidine-based small molecule two-photon fluorescent probe (ELP1 ) for monitoring vesicle transport from the ER to lysosome in live cells. Two-photon microscopy imaging studies indicated that this probe initially localized in the ER and subsequently transferred to lysosomal compartments through vesicular transport. These results may provide an effective tool for studying trafficking-related biology and pathology in real-time.